2020
DOI: 10.2147/rmhp.s235580
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Agriculture and Foreign Remittances in Mitigating Rural Poverty: Empirical Evidence from Pakistan</p>

Abstract: Background: This study examines the role of the agriculture and foreign remittances in mitigating rural poverty in Pakistan. Methods: The data used relate to the period 1980-2017 and are sourced from the World Bank and the Economic Survey of Pakistan produced annually by the Ministry of Finance. The ARDL technique was used to calculate the effects of agriculture and foreign remittances on rural poverty. Results: The results of this study indicate that agriculture helps to mitigate rural poverty in the long run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Correspondingly, Gandi conducted a study of nurses in selected states of Nigeria. The findings of that study support our study and suggest that occupational stress is a significant element in reducing the sustainable work performance of employees [49], so OS at the workplace is costly for organizations [50]. Unhappy or disengaged employees cost companies billions of dollars each year in lost revenues, settlements, and other damages.…”
Section: Discussionsupporting
confidence: 83%
“…Correspondingly, Gandi conducted a study of nurses in selected states of Nigeria. The findings of that study support our study and suggest that occupational stress is a significant element in reducing the sustainable work performance of employees [49], so OS at the workplace is costly for organizations [50]. Unhappy or disengaged employees cost companies billions of dollars each year in lost revenues, settlements, and other damages.…”
Section: Discussionsupporting
confidence: 83%
“…It has been empirically verified that agriculture is the primary source of income in developing countries, and people's livelihood depends on it. Agriculture production is a critical entry-point and more useful for poverty reduction in developing countries (Christiaensen et al 2011, Liu et al 2020. Whereas cereal production accounts for nearly one-third of the total caloric intake in the South Asian countries (Mughal and Sers, 2020); thus, considered an essential factor of food security of these economies (Kropff & Morell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Under the first category, studies have mainly used aggregated government expenditure or government size which consider government expenditure as a percentage of gross domestic product (GDP). Using DOLS, FMOLS, and GMM techniques, Liu et al (2020) demonstrated that increase in aggregate government expenditure reduces rural poverty incidence in Pakistan between 1980. Milovich (2018 included government expenditure as a control variable while examining the Fig.…”
Section: Brief Review Of Relevant Literaturementioning
confidence: 99%